Exchanging “Mementos of Death”: Holocaust Remains in Poland and Japan - Zwigenberg Ran; Dziuban Zuzanna (Eastern European Holocaust Studies)
In 1962, a Japanese delegation of peace activists visited Auschwitz-Birkenau where they participated in the annual ceremony commemorating the liberation of the camp. As part of the ceremony, the delegation engaged in an exchange of Hiroshima and Auschwitz “memontos,” receiving from the Polish side, amongst others, an urn containing ashes of the victims of the camp. The exchange was the first of several that included Holocaust urns, most of which are now in Japan, and a part of a much broader phenomenon of material dispersal of human remains instituted by Polish museums established at the former Nazi camps. In this paper, we take a critical look at this practice, its development, directionalities and meanings. Tracing the journey of the urns and their various uses, we argue, reveals the complex politics and cultural landscape of the transnational commemoration of World War II in its very local meanings in Poland, Japan and beyond.